Lung Decortication: Nursing Assessment, Perioperative Care, and Postoperative Rehabilitation Strategies - Alenazi, Norah Mayof Suad; Zainab Habeeb Mohammad Alabdallah; Nawal Awda Faheed Albalawi; Latifah Awad Alrasheedy; Raghdh Sayah Aldhafeeri; Mashaal Badah Al-Sahli; Alaatia Nafea Alrasheedy; Khulud Swayed Ali Alanezy; Halima Mufleh Alrashedi; Mona Salem Alshammari; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Empyema thoracis and chronic pleural diseases impose significant morbidity due to lung entrapment by fibrous pleural rind, leading to restrictive ventilatory defects and persistent infection. Lung decortication remains a definitive surgical intervention to restore lung expansion and pleural mechanics. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> To review the indications, contraindications, operative principles, and nursing strategies associated with lung decortication, emphasizing multidisciplinary care and postoperative rehabilitation. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive literature-based analysis was conducted, integrating anatomical, physiologic, and clinical perspectives. The review synthesizes operative techniques (open thoracotomy, VATS, robotic approaches), perioperative preparation, equipment requirements, and nursing roles across the care continuum. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Lung decortication effectively removes the fibrous pleural peel, enabling lung reexpansion, improving compliance, and reducing infection risk. Indications include chronic empyema, organized hemothorax, and fibrothorax, while contraindications encompass nonviable lung parenchyma, bronchial stenosis, and uncontrolled systemic infection. Postoperative success hinges on pain control, chest tube management, pulmonary physiotherapy, and vigilant monitoring for complications such as hemorrhage, air leaks, and sepsis. Evidence supports minimally invasive approaches (VATS) for early-stage disease, with comparable outcomes to thoracotomy in selected cases. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Lung decortication is a physiologically restorative procedure that demands precise surgical execution and coordinated multidisciplinary care. Optimal outcomes depend on timely intervention, rigorous patient selection, and structured postoperative rehabilitation to prevent complications and enhance functional recovery.